Strategies for dragline rope life extension - Kuruppu, Mahinda; Dayawansa, D.; Mashiri, F. (The Reading Matrix Inc. (CD ROM volume), 2007)
Draglines are the work horses that are used extensively in the removal of overburden thereby exposing valuable coal seams in open cut mining in the Bowen Basin in Australia. This paper looks at some of the important issues that can strategically be addressed in order to improve maintenance management of dragline wire ropes. The paper looks at the operational, maintenance practice, material and manufacture and design issues and how they influence the fatigue life of dragline wire ropes. These issues are used to address the maintenance of hoist, drag, IBS and suspension ropes. An improved understanding and management of ropes and rope subsystems through detailed rope inspections is proposed.